A STUDY ON ENVIRONMENTAL AND SOCIO-ECONOMIC ANALYSIS OF ARIYALUR CEMENT CITY, TAMILNADU, INDIA - SATHEESH KUMAR PURUSHOTHAMAN, JANANI SELVAM , VASANTHY MUTHUNARAYANAN (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The economic cost of urban air pollution is measured by considering household health production function model which consists of health production function, demand function for mitigating activities and demand function for averting activities. To supplement the analysis of cost of illness approach, the WTP based on the contingent valuation survey is also employed. The ordered logistic regression model is used to analyze the factors affecting willingness to pay for reducing urban air pollution. The total suspended particulate matter (TSPM or PM10) and the respirable suspended particulate matter (RSPM or PM2.5) are considered as criteria pollutants. It is found that PM10and PM2.5 concentration has exceeded the NAAQS in all the monitoring stations of study area. It is two to three times higher than the average annual standard.